KEPEMIMPINAN DEMOKRATIS PERSPEKTIF IBNU KATSIR DAN RELEVANSINYA DALAM TATA KELOLA KEPENDIDIKAN - Lintang Laila Putri Sholikhah; Rz. Ricky Satria Wiranata (Program Studi Manajemen Pendidikan Islam, 2025)
This study discusses democratic leadership in QS Ali Imran:159 perspectives of Ibn Katsir through the interpretation of Al-Quran Al-Adzim and its relevance to educational governance at STAIT Yogyakarta. The background of this research is focused on the importance of applying democratic leadership values in educational institutions, which is expected to improve the quality of education management. The purpose of the study is to identify Ibn Katsir's thoughts on democratic leadership and relate it to practice at STAIT Yogyakarta. The method used is qualitative, through a literature study approach on the tafsir book Al-Qur'an Al-Adzim by Ibn Katsir and structured interviews with the head of the study program, lecturers, educators, and students. The results of the study show that there are three main values of democratic leadership according to Ibn Katsir: gentleness, empathy, and deliberation. From these results, it was concluded that the values of democratic leadership put forward by Ibn Katsir are relevant in educational governance at STAIT Yogyakarta, so that it can support the development of a more participatory learning environment